2019
DOI: 10.1103/physreva.99.042320
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state entanglement and coherence of two coupled qubits in equilibrium and nonequilibrium environments

Abstract: We analytically and numerically investigate the steady-state entanglement and coherence of two coupled qubits each interacting with a local boson or fermion reservoir, based on the Bloch-Redfield master equation beyond the secular approximation. We find that there is non-vanishing steady-state coherence in the nonequilibrium scenario, which grows monotonically with the nonequilibrium condition quantified by the temperature difference or chemical potential difference of the two baths. The steady-state entanglem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…In other words, the quantum state of each system component such as a particle or quibit cannot be described independently from the rest of the system.Entanglement can be quantified by concurrence for low dimensional systems and negativity for high dimensional systems Zyczkowski et al, 1998). It has recently been shown that steady state entanglement can be enhanced by nonequilibriumness, characterized by a temperature difference or chemical potential difference between environments (Eisler and Zimboras, 2005;Lambert et al, 2007;Quiroga et al, 2007;Sinaysky et al, 2008;Wang et al, 2018;Wu and Segal, 2011). It is worth mentioning that the off-diagonal elements of the steady state density matrix in the localized basis is zero when nonequilibrium voltage, and therefore flux, is zero.…”
Section: Nonequilibrium Quantum Transports In Biomoleculesmentioning
confidence: 99%
“…In other words, the quantum state of each system component such as a particle or quibit cannot be described independently from the rest of the system.Entanglement can be quantified by concurrence for low dimensional systems and negativity for high dimensional systems Zyczkowski et al, 1998). It has recently been shown that steady state entanglement can be enhanced by nonequilibriumness, characterized by a temperature difference or chemical potential difference between environments (Eisler and Zimboras, 2005;Lambert et al, 2007;Quiroga et al, 2007;Sinaysky et al, 2008;Wang et al, 2018;Wu and Segal, 2011). It is worth mentioning that the off-diagonal elements of the steady state density matrix in the localized basis is zero when nonequilibrium voltage, and therefore flux, is zero.…”
Section: Nonequilibrium Quantum Transports In Biomoleculesmentioning
confidence: 99%
“…Equations ( 1) rely on the Born-Markov approximation, which is known to be very accurate for quantum optical systems [6]. Significantly, we do not assume the validity of the secular approximation, which cannot be justified for nearly degenerate energy levels [25][26][27][28][40][41][42][43][44][45][46]. This approximation is equivalent to setting p = 0 in Eqs.…”
mentioning
confidence: 99%
“…(1), which eliminates the population-to-coherence coupling terms and hence Fano coherences (see below). Several authors have shown that nonsecular BR equations [25,40,[42][43][44][45][46] and related Lindblad-form master equations [47] generally provide a more accurate description of open quantum system dynamics than secular rate equations.…”
mentioning
confidence: 99%
“…For n > 0 , the populations can be obtained by Q i (i=1,2,4) and the coherence can be extracted from Q 3 . Recall that the off-diagonal elements of the initial state i.e., ρ 23 and ρ 32 demonstrate the initial coherence between the two qubits that gradually disappear due to the decoherence process 51 . In non-equilibrium condition, during the interaction, these elements still exist, while in the steady state (equilibrium) condition they vanish.…”
Section: Equilibrium Populations and Coherencementioning
confidence: 99%